Numerical simulation of the effect of geometric parameters on silicone airway stent migration - Farahani, Maryam Mazraehei; Bakhtiyari, Arman; Beshkoofe, Saed; Kajbafzadeh, Abdolmohammad; Kiani, Arda; Eskandari, Amir Hossein; Baniassadi, Majid; Baghani, Mostafa (Frontiers in Mechanical Engineering, 2023)
At present, endotracheal stenting has become critical in treating respiratory diseases. Due to the COVID-19 pandemic in recent years, many patients had stenosis because of long-term intubation and silicone stents can be used to treat tracheal stenosis in these patient. Standard airway stents are silicone tubes that provide immediate relief but are prone to migration. In this work, we design different silicone stents and analyze them into a tracheal to evaluate silicone airway stents' performance to overcome undesired migration. A finite element model of a tracheal was employed to evaluate anti-migration forces in each stent. The geometry of the trachea is brought from computerized tomography (CT) scan of chest of a 68 years old healthy man. The results are shown based on the least migration of stents based on anti-migration forces.Also, the conditions of stent placement it has been considered based on two different assumed friction factors, and the importance of choosing the type of silicone for stent construction has been analyzed. The results show that increasing the diameter of the stent reduces the displacement and migration of it in the trachea. Furthermore, the 23 mm stent with a 45º angle revealed the best implementation against compression under the impact of respiratory pressure difference.